2018
DOI: 10.7717/peerj.5538
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin deficiency is associated with mortality and impaired organ function in septic pediatric patients: a retrospective study

Abstract: BackgroundSepsis remains a major problem in intensive care medicine. It is often accompanied by coagulopathies, leading to thrombotic occlusion of small vessels with subsequent organ damage and even fatal multi-organ failure. Prediction of the clinical course and outcome—especially in the heterogeneous group of pediatric patients—is difficult. Antithrombin, as an endogenous anticoagulant enzyme with anti-inflammatory properties, plays a central role in controling coagulation and infections. We investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…23 A low AT level in septic children is a good prognostic marker for MODS and is associated with higher mortality. 27 In the present study, median AT activity at day 0 was significantly lower for patients <6 months of age, compared to patients >6 months of age (35.5% and 45.5%, P ¼ .005). However, median c-AT activity corrected by an age-equivalent AT activity of <6 months of age was almost equal to that of patients >6 months of age (46.8% and 43.3%, P ¼ .980).…”
Section: Discussionsupporting
confidence: 43%
“…23 A low AT level in septic children is a good prognostic marker for MODS and is associated with higher mortality. 27 In the present study, median AT activity at day 0 was significantly lower for patients <6 months of age, compared to patients >6 months of age (35.5% and 45.5%, P ¼ .005). However, median c-AT activity corrected by an age-equivalent AT activity of <6 months of age was almost equal to that of patients >6 months of age (46.8% and 43.3%, P ¼ .980).…”
Section: Discussionsupporting
confidence: 43%
“…They demonstrated that antithrombin optimized coagulation and served as a potential regulator of inflammatory processes and subsequent tissue damage. 20 Therefore, antithrombin supplementation may be more effective in patients with hypoalbuminemia, rather than in those with normal albumin levels. Taken together, our findings suggest that antithrombin has a diminished effect in patients with normal albumin levels, which indicates that antithrombin supplementation should be reserved for patients with reduced serum albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 Increased thrombin generation in antithrombin-deficient patients has also been reported. 40 Another possibility is that andexanet alfa treatment may also inhibit the endogenous heparan sulfate glycosaminoglycan (GAGs) complexes with endothelium bound antithrombin. 41 Taken together, andexanet alfa produces additional effects on endogenous modulators which regulates hemostasis including TFPI, antithrombin, GAGs and may also influence other heparin like mediators.…”
Section: Discussionmentioning
confidence: 99%